Endocytosis-like protein uptake in the bacterium Gemmata obscuriglobus - Lonhienne, Thierry G. A. (National Academy of Sciences, 2010)
Endocytosis is a process by which extracellular material such as macromolecules can be incorporated into cells via a membrane-trafficking system. Although universal among eukaryotes, endocytosis has not been identified in Bacteria or Archaea. However, intracellular membranes are known to compartmentalize cells of bacteria in the phylum Planctomycetes, suggesting the potential for endocytosis and membrane trafficking in members of this phylum. Here we show that cells of the planctomycete Gemmata obscuriglobus have the ability to uptake proteins present in the external milieu in an energy-dependent process analogous to eukaryotic endocytosis, and that internalized proteins are associated with vesicle membranes. Occurrence of such ability in a bacterium is consistent with autogenous evolution of endocytosis and the endomembrane system in an ancestral noneukaryote cell.